RESILIENCE: PROTECTIVE FACTOR AND OUTCOME (LITERATURE REVIEW) - Wiwik Triwidiyanti (Journal of Social Science, 2026)
Objective: Resilience is an individual's ability to maintain adaptive functioning and recover optimally after facing stress, difficulties, or psychosocial risk experiences. The study aims to explore the dynamic nature of resilience and identify the factors influencing it. Method: The research method used is a literature review, with the literature for this study accessed by the author from electronic document providers such as Google Scholar, Scopus, EBSCO, and Science Direct. The researcher searched for literature using the keywords "resilience, resilience factor, resilience protective factor, resilience risk factor, resilience antecedent, resilience outcome.” Results: The presence of protective factors, such as personal competence, self-efficacy, self-esteem, optimism, family support, and social support systems, plays an important role in increasing resilience, while risk factors such as stress, anxiety, and psychological pressure are negatively correlated with it. High levels of resilience are associated with better mental and physical health, subjective well-being, and optimal quality of life. Novelty: The study highlights the dynamic nature of resilience as an evolving process influenced by both internal and environmental factors. It emphasizes the significant role of protective factors like self-efficacy and social support in fostering resilience, and their positive impact on mental health and quality of life, offering a more nuanced understanding of resilience beyond being a fixed trait.